NDT-Defect Detection on Concrete using Ultrasonic: A Review - Farah Aina Jamal Mohamad; Ruzairi Abdul Rahim; Nasarudin Ahmad; Sallehuddin Ibrahim; Mohd Hafiz Fazalul Rahiman; Nur Arina Hazwani Samsun Zaini; Navintiran; Syarfa Najihah Raisin; Fatinah Mohd Rahalim; Juliza Jamaludin (MyCT Publishers, 2024)
Non-Indexed Publication